Association between polymorphisms of OGG1, EPHA2 and age-related cataract risk: a meta-analysis. Issue 1 (December 2016) - Zhang, Hongxu; Zhong, Jianguang; Bian, Zhenyu; Fang, Xiang; Peng, You; Hu, Yongping
Abstract Background Evidences have identified the correlation of 8-oxoguanine DNA glycosylase-1 (OGG1) and eph-receptor tyrosine kinase-type A2 (EPHA2) polymorphisms in age-related cataract (ARC) risk. However, the results were not consistent. The objective of this study was to examine the role of these two gene polymorphisms in ARC susceptibility. Methods Eligible case–control studies published between January 2000 and 2015 were searched and retrieved in the electronic databases. The odds ratio with 95 % confidence interval (CI) was employed to calculate the strength of the relationship. Results We totally screened out six articles, including 5971 cataract patients and 4189 matched controls. Three variants were contained (OGG1 rs1052133; EPHA2 rs7543472 and rs11260867). For OGG1 rs1052133, we detected a significant correlation between OGG1 polymorphism and ARC risk under the heterogenous model (CG vs. CC: OR = 1.34, 95 % CI = 1.06–1.70, P  = 0.01) and dominant model (GG+CG vs. CC: OR = 1.45, 95 % CI = 1.16–1.81, P  = 0.001), especially in patients with cortical cataract of subgroup analysis by phenotypes (P  < 0.05). For EPHA2 rs7543472 and rs11260867, we did not find a positive association between these two mutations and ARC susceptibility in total cases. Subgroup analysis by phenotypes of cataract showed that only in cortical cataract, genotypes of rs7543472 under the allele model, homogenous model and recessive model; genotypes of rs11260867 under the heterogenous model and dominant model were associated with ARC risk. Conclusions OGG1 rs1052133 (CG and CG+GG genotypes) might be risk factor for ARC, particularly in cortical cataract risk. EPHA2 rs7543472 (T allele and TT genotype) and rs11260867 (CG and GG+CG genotypes) might be associated with cortical cataract.